Barriers and facilitators of retention in care after cervical cancer screening: patients’ and healthcare providers’ perspectives - Owokuhaisa, Judith; Turyakira, Eleanor; Ssedyabane, Frank; Tusubira, Deusdedit; Kajabwangu, Rogers; Musinguzi, Pius; Galiwango, Martin; Randall, Thomas C.; Kakongi, Nathan; Castro, Cesar M.; Atukunda, Esther C.; Maling, Samuel (BMC Women's Health, 2024)
Background: Cervical cancer continues to threaten women’s health, especially in low-resource settings. Regular follow-up after screening and treatment is an effective strategy for monitoring treatment outcomes. Consequently, understanding the factors contributing to patient non-attendance of scheduled follow-up visits is vital to providing high-quality care, reducing morbidity and mortality, and unnecessary healthcare costs in low-resource settings. Methods: A descriptive qualitative study was done among healthcare providers and patients who attended the cervical cancer screening clinic at Mbarara Regional Referral Hospital in southwestern Uganda. In-depth interviews were conducted using a semi-structured interview guide. Interviews were audio-recorded, transcribed verbatim, and thematically analysed in line with the social-ecological model to identify barriers and facilitators. Results: We conducted 23 in-depth interviews with 5 healthcare providers and 18 patients. Health system barriers included long waiting time at the facility, long turnaround time for laboratory results, congestion and lack of privacy affecting counselling, and healthcare provider training gaps. The most important interpersonal barrier among married women was lacking support from male partners. Individual-level barriers were lack of money for transport, fear of painful procedures, emotional distress, and illiteracy. Inadequate and inaccurate information was a cross-cutting barrier across the individual, interpersonal, and community levels of the socio-ecological model. The facilitators were social support, positive self-perception, and patient counselling. Conclusions: Our study revealed barriers to retention in care after cervical cancer screening, including lack of partner support, financial and educational constraints, and inadequate information. It also found facilitators that included social support, positive self-perception, and effective counselling.
Keywords: Cancer; Cervix; Screening; Loss to follow-up; Retention in care; Barriers; Facilitators